2001
DOI: 10.1182/blood.v98.7.2028
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic and hematopoietic stem cells express a novel SH2–containing inositol 5′-phosphatase isoform that partners with the Grb2 adapter protein

Abstract: IntroductionEngagement of receptors on the surface of mammalian cells results in the activation of phosphatidylinositol 3-kinase (PI3K) and phosphorylation of phosphatidylinositols on the cytoplasmic side of the cell membrane. 8,15 The generation of phosphatidylinositol 3,4,5-trisphosphate (PI 3,4,5 P 3 ) by PI3K contributes to the activation of signaling pathways that drive cell proliferation. [4][5][6][7] Removal of the phosphate group from the D5 position of phosphatidylinositols by the SH2-containing inosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 56 publications
4
90
0
Order By: Relevance
“…How general such restricted pathway activation is for stem cells is unclear. However, it is interesting that variant SHIP and Gab1 signalling molecules lacking subcellular localization motifs have been identified in haematopoietic and ES cells (Tu et al, 2001;Burdon et al, 2002).…”
Section: Teratocarcinomas and Es Cellsmentioning
confidence: 99%
“…How general such restricted pathway activation is for stem cells is unclear. However, it is interesting that variant SHIP and Gab1 signalling molecules lacking subcellular localization motifs have been identified in haematopoietic and ES cells (Tu et al, 2001;Burdon et al, 2002).…”
Section: Teratocarcinomas and Es Cellsmentioning
confidence: 99%
“…SHIP is primarily expressed in hemopoietic cells (9,10), but it can also be expressed in mouse embryonic fibroblasts (11). The SHIP locus also encodes a stem cell-specific isoform called s-SHIP that lacks the Src homology 2 domain and is expressed by pluripotent stem cells and tissue-specific stem cells (11,12). SHIP's role in signal transduction allows it to regulate cell survival, proliferation, apoptosis, and homeostasis of certain hemopoietic cell types (7,(13)(14)(15)(16), as well as primitive stem cell populations (11,12,17,18).…”
Section: G Raft-vs-host Disease (Gvhd)mentioning
confidence: 99%
“…The SHIP locus also encodes a stem cell-specific isoform called s-SHIP that lacks the Src homology 2 domain and is expressed by pluripotent stem cells and tissue-specific stem cells (11,12). SHIP's role in signal transduction allows it to regulate cell survival, proliferation, apoptosis, and homeostasis of certain hemopoietic cell types (7,(13)(14)(15)(16), as well as primitive stem cell populations (11,12,17,18). Analysis of SHIP-deficient mice revealed that this protein also has a prominent role in the immune system (7,14,15,19).…”
Section: G Raft-vs-host Disease (Gvhd)mentioning
confidence: 99%
“…This enzyme lacks the SH2 domain of the 145-kDa SHIP1 isoform (present in mature cells and referred to as the complete isoform SHIP1). sSHIP is not tyrosine phosphorylated [34,35]. It is, however, present in a membrane fraction due to its interaction with Grb2.…”
Section: Discovery Of Ship1/2 In a Complex Of Tyrosine Phosphorylatedmentioning
confidence: 99%